Synthesis and Physico-Chemical Properties of Nanosized Vanadium Phosphorus Oxide, and its Use as Catalyst in Selective Oxidation of n-Butane to Maleic Anhydride - Nawi @ Mohamed, Nurul Suziana (2011)
In this study, nanosized vanadium phosphorus oxide (VPO) catalyst was synthesized via a new organic route. The synthesized nanosized VPO catalyst was compared with conventional VPO catalyst which was prepared via conventional organic route. Besides, various metal dopants i.e zirconium (Zr), zinc (Zn), nickel (Ni), molybdenum (Mo), manganese (Mn), niobium (Nb), iron (Fe), copper (Cu), chromium (Cr), cerium (Ce) and cobalt (Co) also used in this study in order to investigate the role of metal dopants on the nanosized VPO catalyst. The physico-chemical properties of the synthesized catalysts were characterized by using x-ray diffraction (XRD), BET surface area measurement, redox titration, inductively coupled plasma –atomic emission spectroscopy (ICP-AES), scanning electron microscopy (SEM), and transmission electron microscopy (TEM) and temperature programmed reduction in H2. The catalytic properties of the synthesized catalysts were carried out by using an on-line microreactor system. Results show that the nanosized VPO catalysts successfully synthesized via new organic route in far less duration i.e. 13 h compared to conventional organic route i.e. 109 h with good properties of the VPO catalysts. XRD pattern of the synthesized VPO catalysts showed the major peak of pyrophosphate, (VO)2P2O7 phase. However, the major peaks for nanosized VPO catalyst especially for (020), (204) and (221) phases are shown to be more prominent than those of conventional VPO catalyst. Besides, the new organic route also produced high surface area VPO catalysts with 5 times larger than conventional VPO catalyst. Formation of thin and increasing of platelets for nanosized VPO catalyst was also observed in SEM micrographs. Furthermore, particle size of this catalyst was found in nanoscale range (40-60 nm) as was proved by TEM. High amount of O2- and O- species removed for nanosized VPO was obtained by H2-TPR directly lead to a significant improvement in n-butane conversion at 673 K and also at lower temperatures (643 and 623 K) with higher maleic anhydride (MA) selectivity for the respective temperatures. The introduction of various metal dopants into the lattices of VPO catalyst did not alter the phase of hemihydrate precursors and the final catalysts. There are small variations can be observed on the surface area, redox titration and average vanadium oxidation state for the nanosized doped VPO catalysts compared to the nanosized undoped VPO catalyst. On the other hand, the incorporation of 1% Nb, Ni, Ce, Zr, Zn, Cr and Fe successfully reduced the particle size below than 40 nm. Moreover, the certain metal dopants can induced the amount of oxygen O2- and O- species removed especially for Ce, Cr and Ni doped catalysts. These fascinating features gave drastic increment for n-butane conversion and maleic anhydride (MA) selectivity at higher and lower temperatures (673, 643 and 623 K). The selectivity of maleic anhydride (MA) of all the synthesized nanosized VPO catalysts at lower temperatures i.e. 643 and 623 K are comparable with the conventional VPO catalyst at higher temperature, 673 K.